2003
DOI: 10.1159/000070626
|View full text |Cite
|
Sign up to set email alerts
|

A New Mutation of 5-Alpha-Reductase Type 2 (A62E) in a Large Egyptian Kindred

Abstract: Objective: To describe the clinical, biological and molecular data in a large Egyptian kindred with 5α-reductase deficiency. Patients and Methods: Three patients with ambiguous genitalia were referred at the ages of 20, 9 and 2 years, respectively. In all cases, parents were first cousins. Basal and post-HCG stimulation plasma levels of testosterone and dihydrotestosterone were determined. Direct sequencing and restriction site analysis were applied for patient and family study. Results: A homozygous alanine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Differential diagnosis of 5a-reductase deficiency with PAIS is difficult since the clinical signs and biological parameters are similar. In most but not all patients, low plasma DHT levels and an elevated plasma T ⁄ DHT ratio after hCG stimulation testing is observed (Imperato-McGinley et al, 1986;Boudon et al, 1995a,b;Hafez et al, 2003;Mazen et al, 2003a). However, as we reported previously (Boudon et al, 1995a,b;Mazen et al, 2003b), SRD5A2 mutations have been identified in patients with a non-significant increase in plasma T ⁄ DHT.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Differential diagnosis of 5a-reductase deficiency with PAIS is difficult since the clinical signs and biological parameters are similar. In most but not all patients, low plasma DHT levels and an elevated plasma T ⁄ DHT ratio after hCG stimulation testing is observed (Imperato-McGinley et al, 1986;Boudon et al, 1995a,b;Hafez et al, 2003;Mazen et al, 2003a). However, as we reported previously (Boudon et al, 1995a,b;Mazen et al, 2003b), SRD5A2 mutations have been identified in patients with a non-significant increase in plasma T ⁄ DHT.…”
Section: Introductionsupporting
confidence: 68%
“…, 1993). Various authors have suggested that SRD5A2 gene mutations can be separated into two broad categories, including recurrent mutations, as they have been identified in various ethnic groups or reflect a founder gene effect (Hafez et al. , 2003; Skordis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the SRD5A2 gene lead to a reduction in enzymatic activity and DHT production [6], causing defective masculinization in the forms of hypospadia and microphallus [7,8]. To date, more than 50 different mutations have been reported in patients with 5α-reductase type 2 deficiency, and missense and nonsense mutations were frequently reported [4,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…The primordial role of 5α-reductase enzyme activity was first demonstrated in animal studies, until a cluster of male pseudohermaphrodite patients, in whom deficient virilisation was attributable to an almost complete lack of this enzyme activity, was described [1, 2]. A number of deletions and point mutations in the SRD5A2 gene, which encodes the 5α-reductase type 2 enzyme [3], had been demonstrated in patients with variable clinical and biochemical phenotypes [4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19]. This variability may depend on the patient’s age at the time of the study, availability of testicular androgen production studies, of genital skin for enzyme activity determination in fresh tissue or in its cultured fibroblasts and on the effects of the different mutations on protein synthesis and function.…”
Section: Introductionmentioning
confidence: 99%